2016
DOI: 10.15561/20755279.2016.0103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of information technologies on technical fitness of students in sport-oriented physical education

Abstract: Abstract. Purpose: to determine influence of information technologies in sport-oriented physical education on technical fitness of students, practicing football indoors. Material: in the researches students (boys -n=40) of 18-20 years' age participated. Standard tests on physical condition were used. For determination of motor skills and abilities we used: juggling with ball; kick in pre-set sector of goal; shuttle run 4 х 10 meters with dribbling; kick for distance. Results: structural model of sport-oriented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 19 publications
1
32
0
13
Order By: Relevance
“…Consider the example of the provisions of basic movements for a person, that is, those who helped him to survive in the course of evolution [Ryepko, 2013;Kozina et al, 2016]. Among these movements -the innate grasping reflex as well as crawling, climbing, including -for the vertical support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider the example of the provisions of basic movements for a person, that is, those who helped him to survive in the course of evolution [Ryepko, 2013;Kozina et al, 2016]. Among these movements -the innate grasping reflex as well as crawling, climbing, including -for the vertical support.…”
Section: Resultsmentioning
confidence: 99%
“…[Ryepko, 2013;Kozina et al, 2016] the structure of the physical preparation of young climbers has been developed. It has been developed and adapted program of complex preparation of young climbers 6-7 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis of scientific literature data [40,41] was revealed that the problem of individual distinctions has rich history and is beyond far the theory and a technique of physical training and sport. From this point of view our work is expansion and addition of available knowledge of individual human nature.…”
Section: Discussionmentioning
confidence: 99%
“…The third direction of researches is connected with development of the interactive technologies [41] permitting to increase the various aspects of training process to qualitatively new level.…”
Section: Pedagogics Psychologymentioning
confidence: 99%